Argentina and the new (old) dilemmas of international insertion: Free trade agreements or strengthening of the internal market with a regional projection - Paikin, Damián (2018)
This paper analyzes the formal-legal and economic potentials of a possible entry of Argentina to the Pacific Alliance. Two questions need to be answered. First: Would it be possible to be part of these two integration schemes? Second: What would Argentina specifically benefit from by joining the Alliance? For this purpose, a comparative exercise is carried out to perceive to what extent the member countries of the Pacific Alliance benefited from it, and which sectors within them, in order to foresee what might happen in the case of Argentina.